As categorias e os conceitos da geomorfologia encontrados nos livros didáticos do ensino médio - Boico, Kamila da Silva Raimundo (2009)
This study discusses the approach to categories and concepts related to Geomorphology in four teaching books written for high school students. We present not only the definitions for the subject studied in these works, but also take into account the images, figures, diagrams and maps presented, whose function is to aid in the explanation of the processes that occur inside the earth and on its surface, which in turn come to influence the forms of terrestrial relief. For the production of this analysis, we used respected works that deal with the dynamics studied by Geomorphology, as in the case of the Dictionary of Geology and Geomorphology, by Guerra (1987) and Understanding the Earth, compiled by Teixeira (2001). We also used an interview with Professor Gil Sodero de Toledo, who told us a little about the lectures that he gave in the University of Sao Paulo, and his reports were important to this research, given that he commented on the professors of Geography, on the participation that he had in formulating the Curriculum Guidelines of the State of Sao Paulo in 1986, on teaching books, amongst other subjects that involve the theme of this work